Leishmania donovani Secretory Mevalonate Kinase Regulates Host Immune Response and Facilitates Phagocytosis - Bamra, Tanvir; Shafi, Taj; Das, Sushmita; Kumar, Manjay; Dikhit, Manas Ranjan; Kumar, Ajay; Kumar, Ashish; Abhishek, Kumar; Pandey, Krishna; Sen, Abhik; Das, Pradeep (Frontiers in Cellular and Infection Microbiology, 2021)
Visceral Leishmaniasis is a persistent infection, caused by Leishmania donovani in Indian subcontinent. This persistence is partly due to phagocytosis and evasion of host immune response. The underlying mechanisms involves secretory proteins of Leishmania parasite; however, related studies are meagre. We have identified a novel secretory Leishmania donovani glycoprotein, Mevalonate kinase (MVK) and shown its importance in parasite internalization and immuno-modulation. In our studies, MVK was found to be secreted maximum after 1hour temperature stress at 37ºC. Its secretion was increased by 6.5-fold in phagolysosome-like condition (pH 5.5, 37ºC) than at pH 7.4 and 25ºC. Treatment with MVK, modulated host immune system by inducing interleukin-10 and interleukin-4 secretion, suppressing host’s ability to kill the parasite. Peripheral blood mononuclear cell (PBMC)-derived macrophages infected with mevalonate kinase-overexpressing parasites showed an increase in intracellular parasite burden in comparison to infection with vector control parasites. Mechanism behind the increase in phagocytosis and immunosuppression was found to be phosphorylation of mitogen-activated protein (MAP) kinase pathway protein, Extracellular signal-regulated kinases- 1/2 and actin scaffold protein, cortactin. Thus, we conclude that Leishmania donovani Mevalonate kinase aids in parasite engulfment and subvert the immune system by interfering with signal transduction pathways in host cells, which causes suppression of the protective response and facilitates their persistence in the host. Our work elucidates the involvement of Leishmania in the process of phagocytosis which is thought to be dependent largely on macrophages and contributes towards better understanding of host pathogen interactions.